Analisis Pengendalian Persediaan Bahan Baku dengan Menggunakan Metode Economic Order Quantity (EOQ) di PT. XYZ - Lulu Firyal Amalia; Ade Momon S (Jurnal Ilmiah Wahana Pendidikan, 2022)
The manufacturing industry is a businesses that are growing rapidly with intense competition. In order for industrial activities to run effectively and efficiently, problems in the production process need to be considered. The solution to handle it is to do the right management of procurement. The purpose of this study is to determine the comparison between the total cost of raw material inventory using the policy of PT. XYZ and using the Economic Order Quantity (EOQ) method, so the company can choose which method is more effective to implement. This research is a quantitative research and the data collection technique is by conducting literature studies, interviews and direct observation. The research results obtained from this study are calculations using the EOQ method which have more optimal results compared to the policies implemented by PT. XYZ. This is evidenced by the frequency of orders using the EOQ method which is less than 6 times, with a difference of 3 times compared to the current policy. In addition, the cost of inventory is also less, amounting to Rp.6.001,685 with a difference of Rp.541.267 compared to the policies implemented in the company.